Reactive interdiffusion of an Al film and a CoCrFeNi high-entropy alloy - Z.Q. Zhang; S.V. Ketov; S. Fellner; H.P. Sheng; C. Mitterer; K.K. Song; C. Gammer; J. Eckert (Materials & Design, 2022)
Diffusion plays a significant role in phase formation and transformation in solid-state alloys. In order to determine the influence of element diffusion on the phase formation and transition behavior in a high-entropy alloy (HEA), a systematic study on the reactive diffusion of Al and a CoCrFeNi HEA was carried out. It is demonstrated that thermodynamic and kinetic effects play a coupled role in the phase evolution in the HEA, among which the thermodynamic effect governs the evolution of major phases. The diffusion direction of the elements is controlled by the Gibbs free energy gradient in front of the interface, while the sluggish diffusion effect does not play a dominant role during reactive diffusion. At an annealing temperature of 773 K, the enthalpy of mixing dominates the total energy and therefore has a significant impact on the phase evolution during reactive diffusion.